Perception of Europe in the speeches by the President of Republic of Croatia Franjo Tudjman (1991-1999) - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article deals with the discursive process through which Croatia framed its so-called “return to Europe” throughout the 1990s. T he author explores how Franjo Tudjman perceived Europe and European values by defining Croatian national identity in the strict opposition to the Balkan or Yugoslav identity. The post-communist government, which came to power after the first democratic elections in 1990, made use of the pre-communist historical-national narratives to legitimize itself and unify all ethnic Croats against the military threat. Even though since the beginning of the 1990s the Croatian president had declared his desire to join the European Union (EU ) as a visible symbol of the so called Europeanization process, a nationalist and isolationist attitude dominated both his political discourse and the intellectual debate. Europe was associated with the ontological values dedicated to the Western civilization rather than with such principles as democratization or the protection of human and minority rights, promoted by the EU . I n order to show the main directions within the F. Tudjman’s discourse, I used the analysis method focusing on his speeches and other works.